Hidden Handicaps of Benchmarking: Impact of the Choice of Industry Classification Taxonomy on Peer Group Based Evaluations - Banasiewicz, Andrew (Journal of Management Policy and Practice, 2023)
Benchmarking is one of the most widely used business assessment tools. It is rooted in the use peer groupframed comparisons geared toward objective assessment of company-specific performance, processes, or threat exposures. A critical aspect of benchmarking is peer group selection – here, it is widely believed that the use of standard industry classification offers an unbiased and uniform benchmark-setting basis. More specifically, the notion of ‘industry segment’ is often implicitly assumed to be definitionally singular, in the sense of being universally defined – that, however, is not the case. There are multiple competing industry definition and classification schemas and cross-taxonomy differences are substantial, which suggest that the choice of industry classification taxonomy can have material impact on the resultant benchmarks, and more importantly, on benchmarking-based evaluations. This article offers an empirical examination of that supposition, built around benchmarking-based assessment of a pharmaceutical company’s exposure to securities litigation; the results offer supporting evidence of material impact of the choice of industry classification schema on benchmark values and the resultant decision-making implications.